Optimization for a centrifugal pump transporting brine using orthogonal design based on CFD-DEM simulation. Issue 2 (January 2021) - Tang, C; Kim, YJ
Abstract: To enhance the reliability of a centrifugal pump transporting brine solutions with crystallization, the effect of impeller geometrical configurations on crystal particle behaviors was investigated by an orthogonal design based on CFD-DEM coupled method. In this work, the main impeller geometrical configurations were set as the blade inlet angle α1, blade outlet angle α2, wrap angle φ, and outlet width b2 . In the meanwhile, the L9 (3 4 ) orthogonal design containing 4 factors with 3 levels was applied in this study. Given the crystal particle features, CFD-DEM coupling method was utilized to study inner flow in a pump with crystal particles. Current results indicated that the blade outlet angle α2 could significantly affect the collisions between particles and blades. Moreover, a low-speed region at the blade pressure side in the optimal impeller has been reduced, declining the probability of the crystal particles adhering to the impeller.